2019
DOI: 10.1111/tpj.14164
|View full text |Cite
|
Sign up to set email alerts
|

A Förster resonance energy transfer sensor for live‐cell imaging of mitogen‐activated protein kinase activity in Arabidopsis

Abstract: The catalytic activity of mitogen-activated protein kinases (MAPKs) is dynamically modified in plants. Since MAPKs have been shown to play important roles in a wide range of signaling pathways, the ability to monitor MAPK activity in living plant cells would be valuable. Here, we report the development of a genetically encoded MAPK activity sensor for use in Arabidopsis thaliana. The sensor is composed of yellow and blue fluorescent proteins, a phosphopeptide binding domain, a MAPK substrate domain and a flexi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 82 publications
(111 reference statements)
1
27
0
Order By: Relevance
“…To determine if the mammalian phosphoacceptor domain present in EKAREV was being targeted by CA-MPK4/6, we mutagenized the threonine residue in EKAREV-BASL thought to behave as the phosphorylation site into an alanine [ 26 , 48 , 60 ]. The resulting mutant version of the biosensor, EKAREV T48A -BASL, showed no increase in FRET efficiency when incubated with either CA-MPK4 or CA-MPK6 ( Figure 2 D, Table 1 ), similar to the results observed when the phosphorylation site of SOMA was mutagenized to an alanine ( Figure S1A,B , Table 1 ) [ 44 , 66 , 67 ]. These results demonstrate that the MAPK-induced FRET gain observed with EKAREV-BASL is dependent on the threonine present within the EKAREV phosphoacceptor domain and suggest that the increase in FRET efficiency is likely caused by phosphorylation of that threonine by CA-MPK4/6.…”
Section: Resultssupporting
confidence: 66%
See 3 more Smart Citations
“…To determine if the mammalian phosphoacceptor domain present in EKAREV was being targeted by CA-MPK4/6, we mutagenized the threonine residue in EKAREV-BASL thought to behave as the phosphorylation site into an alanine [ 26 , 48 , 60 ]. The resulting mutant version of the biosensor, EKAREV T48A -BASL, showed no increase in FRET efficiency when incubated with either CA-MPK4 or CA-MPK6 ( Figure 2 D, Table 1 ), similar to the results observed when the phosphorylation site of SOMA was mutagenized to an alanine ( Figure S1A,B , Table 1 ) [ 44 , 66 , 67 ]. These results demonstrate that the MAPK-induced FRET gain observed with EKAREV-BASL is dependent on the threonine present within the EKAREV phosphoacceptor domain and suggest that the increase in FRET efficiency is likely caused by phosphorylation of that threonine by CA-MPK4/6.…”
Section: Resultssupporting
confidence: 66%
“…If so, this FRET biosensor had the potential to serve as a plant MAPK docking domain trap. To test this hypothesis, we used an in vitro assay that we previously developed for evaluating candidate plant MAPK FRET biosensors [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Apart from amplitude, calcium signals also vary in duration and frequency, whose impact on kinase activation has not yet been tested. Considering that monitoring CDPK activation in vitro is tricky due to calcium release during material grinding (Seybold et al, 2018), the development of biosensors to monitor kinase activation in vivo as reported for MAPKs will be essential in the future (Zaman et al, 2019). One important limitation of this system is the identification of specific substrates for each kinase isoform.…”
Section: Discussionmentioning
confidence: 99%